2020
DOI: 10.1038/s41598-020-64958-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermal annealing on localization and strain in core/multishell GaAs/GaNAs/GaAs nanowires

Abstract: Core/shell nanowire (NW) heterostructures based on III-V semiconductors and related alloys are attractive for optoelectronic and photonic applications owing to the ability to modify their electronic structure via bandgap and strain engineering. Post-growth thermal annealing of such NWs is often involved during device fabrication and can also be used to improve their optical and transport properties. However, effects of such annealing on alloy disorder and strain in core/shell NWs are not fully understood. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…One can also anneal organic/inorganic semiconductors via rearranging molecules, polymer chain segments, or entire polymer chains into active layer films. Optimizing the annealing temperature and time can either dramatically increase the crystal size from the sub-micrometer scale to several micrometers, or yield different crystals (35).…”
Section: Introductionmentioning
confidence: 99%
“…One can also anneal organic/inorganic semiconductors via rearranging molecules, polymer chain segments, or entire polymer chains into active layer films. Optimizing the annealing temperature and time can either dramatically increase the crystal size from the sub-micrometer scale to several micrometers, or yield different crystals (35).…”
Section: Introductionmentioning
confidence: 99%
“…One can also anneal organic/inorganic semiconductors via rearranging molecules, polymer chain segments, or entire polymer chains into active layer films. Optimizing the annealing temperature and time can either dramatically increase the crystal size from the submicrometer scale to several micrometers or yield different crystals ( 3 5 ).…”
mentioning
confidence: 99%
“…Nanowireswith several shells [134]. From equations (3.2), it may be shown that the dominant strain component is the uniaxial component along the nanowire axis [133].…”
mentioning
confidence: 99%